The impact of the COVID-19 pandemic on the mental health of new mothers in China: A qualitative study of mothers with infants aged 0–1 year old - Zou, Dandan; Chen, Chen (Frontiers in Public Health, 2023)
Background: China has implemented a strict epidemic control policy (ECP) for three years during the COVID-19 pandemic. New mothers are under great psychological pressure to protect themselves against the virus, following the ECP, as well as taking on the main responsibility of raising their children. However, the mental health of this group has been neglected by the public. The aim of this article is to understand the mental health of new mothers during the COVID-19 pandemic. Method: Qualitative research methods were adopted in this study. From October 1st to November 1st in 2022, we conducted in-depth interviews with 36 new mothers in Guiyang, Guizhou, China and used thematic analysis to examine their emotional status, as well as the origins of their negative and positive emotions. Results: (1) New mothers are chronically depressed, feeling anxious and upset. (2) Negative emotions are caused either by the virus or by the ECP. (3) New mothers are mainly anxious about their children's physical health, feeding options, childcare and family income. (4) Positive emotions are reflected by tight parent-child bonds, a better understanding of childcare and an increased ability to perceive risks. Conclusion: The anxiety of new mothers has revealed the shortcomings of the Chinese health system in the emergency management of the mother and child. At the same time, the outbreak is an opportunity to improve the response management capacity of the health system in order to prevent the recurrence of similar problems for mothers and infants.